Estudio del potencial exportador de vino de arazá a los países bajos (2020)
The work consists of the development of a plan to export Arazá wine to the Netherlands, the objective of which is to publicize and make the most of the Arazá's capabilities by transforming it into a product for human consumption. Taking into account the knowledge of International Trade acquired in the career, the work was developed with a broad logistical base applying export costs, Incoterms and taking advantage of the free trade agreement between Colombia and the Netherlands to minimize costs and make its development more viable.